Teacher Perceptions of Making Interactive Questions Using the Quizizz Application In Physics Learning - Fitria Herliana; Yusrizal yusrizal; E Mahsum; S Rizal; Musdar Musdar (Universitas Islam Negeri (UIN) Mataram, 2023)
This study aims to see teacher perceptions of making interactive questions using the Quizizz application. This research was carried out using a training approach, which was carried out for 2 days and added with independent assignments. The sample used was 21 people, with the sampling technique using random sampling. Data collection using a 4-point Likert scale questionnaire consisting of 12 items was carried out at the beginning of the activity and after training—data analysis using descriptive and inferential statistics. The results showed that Science Teachers (Physics) in junior and senior high schools in Sabang City had a perception of the Quizizz application in learning 86.31%, which was classified as very good. Teacher perceptions of knowledge related to Quizizz applications in learning amounted to 84.82%, classified as good. Teacher perceptions of skills in using the Quizizz application in education amounted to 83.04%, classified as good. Teacher perceptions of attitudes towards using the Quzizz application in learning amounted to 91.07%, classified as very good. Teachers have a positive perception of being able to apply this Quizizz application in education because teachers have been equipped with the knowledge and skills gained in training activities, and teachers have a positive attitude towards using this application in the learning process.